Pengaruh Komitmen Organisasi dan Disiplin Kerja Terhadap Kinerja Karyawan BPJS Ketenaga Kerjaan Meulaboh - Batia, Nur; Hajar, Siti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to use a quantitative approach to the phenomena that occur in BPJS Ketenagakerjaan Meulaboh Employees. The Data Method used in this study is the Non Probability Sampling technique with a Sample of 25 Employees at BPJS Ketenagakerjaan Meulaboh. The data used are Primary data and Secondary data. The data analysis techniques that will be used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, Hypothesis Testing using SPSS22 Software and Determination Coefficient. The results of this test state that the Influence of Commitment and Work Discipline has an effect on the Performance of BPJS Ketenagakerjaan Meulaboh Employees.